2017
DOI: 10.1111/bjh.14621
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐chelating therapy with deferasirox in transfusion‐dependent, higher risk myelodysplastic syndromes: a retrospective, multicentre study

Abstract: Iron chelation is controversial in higher risk myelodysplastic syndromes (HR-MDS), outside the allogeneic transplant setting. We conducted a retrospective, multicentre study in 51 patients with transfusion-dependent, intermediate-to-very high risk MDS, according to the revised international prognostic scoring system, treated with the oral iron chelating agent deferasirox (DFX). Thirty-six patients (71%) received azacitidine concomitantly. DFX was given at a median dose of 1000 mg/day (range 375-2500 mg) for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 83 publications
2
19
0
Order By: Relevance
“…Prospective well-designed trials of deferasirox in MF should provide information on the frequency and magnitude of such an effect and examine the potential impact of therapy on other relevant outcomes in MF, such as overall survival, marrow fibrosis, and quality of life [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Prospective well-designed trials of deferasirox in MF should provide information on the frequency and magnitude of such an effect and examine the potential impact of therapy on other relevant outcomes in MF, such as overall survival, marrow fibrosis, and quality of life [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Data on the 18 HR-MDS trials are shown in Table 2. 3,[13][14][15][16][18][19][20][21][22][23][26][27][28][29][30][32][33][34] Chemotherapy: Conventional Chemotherapy Regimens Overall, the prognosis of patients treated with CCRs in realworld settings was poor, particularly with respect to longer-term OS. Among patients receiving CCRs, 2 studies, Bernal et al 13 and Kantarjian et al 23 reported median OS of 12.2 and 34 weeks (3 and 8.5 months), respectively.…”
Section: Higher-risk Mdsmentioning
confidence: 99%
“…The study reported by Musto et al 29 One study (Kantarjian et al 22 ) reported survival for patients who underwent allo-HSCT after chemotherapy (cytarabine with or without topotecan with or without cyclophosphamides, or fludarabine with or without anthracyclines); those who had the procedure while experiencing a first CR had a higher estimated 5-year survival rate (36%) than those who underwent the procedure after a first CR failed (9%).…”
Section: Higher-risk Mdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although time to hematologic improvement observed in our study was particularly late (6 months and 10 months for HI-N and HI-P, respectively), it has to be noted that, although more rarely, hematologic improvement may occur early, 11 even in the setting of higher risk patients. 14 have also to be considered according to previous studies. 27,28 Our work shows some discrepancies in results at 3 months when based on transfusion requirement assessed over a 8-week period compared to IWG criteria for minor erythroid response.…”
Section: Changes In Serum Ferritin Levelsmentioning
confidence: 99%